Community Readiness on Non-Organic Waste Management of Hamlet 3, Kasomalang Kulon Village, Subang District, Indonesia - Yustiani, Yonik Meilawati; Hasbiah, Astri Widiastuti; Yusuf, Mahmud; Alfiah, Taty (Teknik Lingkungan Universitas Islam Indonesia, 2022)
Waste management is a systematic, comprehensive and sustainable activity that includes the reduction and handling of waste. In Kasomalang Kulon Village precisely in Hamlet 3, waste management has not yet been carried out properly. Community education is conducted to gain more awareness of people in handling the waste properly. The purpose of this study is to identify non-organic waste that still has an economic value so that it can be recycled and reduce the amount of waste that enters the waste disposal site. The research also aims to know the readiness of the community in managing waste, and determine the processing needed. Prior to designing the management system, a sampling was conducted using sampling method based on SNI 19-3964- 1994 to identify quantity and type of wastes. The community readiness was investigated by distributing questionnaires following the community education. The survey shows that the solid waste generation is 0.193 kg/person/day for permanent houses and 0.182 kg/person/day for semi-permanent houses and the average weight of garbage generation per day is 68.80 kg. Non-organic waste data from Kasomalang Kulon Village which has an economic value of 32% of the total waste generation which is 3,761 L/d with potency of approximately IDR 425,000 per week. In general, the KAP survey shows that community has a high level of knowledge, positive attitudes and good behavior, which indicates the readiness of the community in managing non-organic waste.